Component suppliers in the commodity battle: Can digital technology in multi-tier supply chains help to transform liabilities into opportunities? - Tobias D. Herbst (International Journal of Business Science & Applied Management (IJBSAM), 2021)
This conceptual study analyzes how digital technologies can create opportunities for component suppliers in multi-tier supply chains facing the issue of commoditization and it develops a strategic framework based on prior studies. This study finds that modularity facilitates the understanding of the dynamics of commoditization and knowledge sharing. Furthermore, modularization drives the asymmetric distribution of information in a multi-tier supply chain. Finally, digital technologies can offer strategic opportunities for targeting different stages of the value chain. Component suppliers should evaluate the criticality of products in new business models and advanced services to reduce the complexity of the landscape of strategic options and, thus, reduce wrong decisions. Managers should encourage general information sharing and open data exchange in a multi-tier supply chain. They should focus on vertical and horizontal partnerships and collaborations to foster the benefits of digital technologies. Conclusively, component suppliers should cooperate to build a counterweight to original equipment manufacturers in the vertical partnership. This study is the first to integrate the benefits of commodities and digital technologies in a strategic framework. It contributes to the literature on competition in the background of commoditization by outlining the concept of information asymmetry within a multi-tier supply chain driven by modularity. Thus, it advances the literature on digital technology and commoditization.
Keywords: 650; multi-tier supply chain; strategy; modularity; servitization; commoditization; digitalization; knowledge-based view